2018
DOI: 10.1590/0102-311x00103117
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidad por diabetes tipo 2 y la implementación del programa PREVENIMSS: un estudio de series de tiempo en México, 1998-2015

Abstract: Type 2 diabetes is the leading cause of morbidity and mortality in the world. In Mexico it is the first cause of mortality, disability, and potential years of life lost due to premature death. The Mexican Institute of Social Security (IMSS) implemented the PREVENIMSS strategy. The aim of the current study was to estimate the program's effect on the mortality trend from type 2 diabetes, based on an interrupted time series analysis. At the beginning of the target period, the diabetes mortality rate was higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Through our qualitative study, interviewing adults with T2D and providers, we identified numerous challenges related T2D care in Mexico that are important to contextualize within the current policy trends in Mexico. In the last decade, several policy frameworks and interventions related to T2D care have been implemented; among them the National Strategy for the Prevention and Control of Overweight, Obesity and Diabetes and the expansion of the Seguro Popular system [23, 24]. This has contributed to a greater emphasis of diabetes in the national policy agenda, leading to an increase in screening for T2D, the establishment of diabetes care centers [25], and the implementation of public policies such as sugar-sweetened beverages taxation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Through our qualitative study, interviewing adults with T2D and providers, we identified numerous challenges related T2D care in Mexico that are important to contextualize within the current policy trends in Mexico. In the last decade, several policy frameworks and interventions related to T2D care have been implemented; among them the National Strategy for the Prevention and Control of Overweight, Obesity and Diabetes and the expansion of the Seguro Popular system [23, 24]. This has contributed to a greater emphasis of diabetes in the national policy agenda, leading to an increase in screening for T2D, the establishment of diabetes care centers [25], and the implementation of public policies such as sugar-sweetened beverages taxation [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Stockholm Diabetes Prevention Program cumulatively reduced DMM by 436 per 10,000 in men and 53 in women over 10 years [ 34 ]. Another study found a long-term effect for the Mexican diabetes prevention program PREVENIMSS with a reduction in DMM of 3.6 per 100,000 per year [ 35 ]. While these effects are higher than our results, this can at least be explained by the fact that ISCHG did not focus on DM prevention but could include a wide range of prevention targets and target groups, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It involves examining the relationship between variables over time, identifying trends, seasonality, and other patterns. Time series analysis has been utilized in public health research and policy-making to assess the impact of interventions, allocate resources effectively, and make informed decisions during disease outbreaks [12]. One of the commonly used time series analysis methods is exponential smoothing.…”
Section: Time Series Analysismentioning
confidence: 99%